ANTIBODY RESPONSE IN MICE TO FOOT AND MOUTH DISEASE (FMD) DNA VACCINE - Arsadita, I Gede Wiraguna; Mahardika, I Gusti Ngurah Kade; Suharsono, Hamong (Buletin Veteriner Udayana, 2025)
Foot and Mouth Disease (FMD) is a highly contagious viral infection in livestock, causing severe economic losses worldwide. While conventional vaccines are widely used, innovative alternative such as DNA vaccines is needed. This study aimed to assess the immunogenicity of a novel DNA vaccine against FMD, encoding the VP0, VP3, VP1, 2A, and 3CPRO genes derived from an Indonesian FMD virus isolate (2022). Female mice were immunized with the vaccine, and antibody responses were evaluated weekly for four weeks using ELISA using synthetic peptide of VP1 as coating antigen. Results demonstrated that the vaccine significantly induced FMD-specific antibodies compared to the control group, with optical density (OD) values consistently higher in vaccinated mice across all time points post vaccination (p < 0.001). However, no significant difference in antibody levels was observed between weeks post-vaccination within the treatment group (p = 0.678), suggesting stable immune activation after the initial response. These findings indicate that the DNA vaccine effectively triggers humoral immunity, supporting its potential as a viable alternative to traditional FMD vaccines. Further research should evaluate its efficacy in target livestock species and optimize delivery methods for field applications.